Epizootic diseases of oysters associated with viral infections - Comps, Michel (American Fisheries Society, 1988)
Virus infections have been associated with major diseases of oysters of the genus Crassostrea. These infections include gill necrosis virus and hemocytic infection virus diseases of the Portuguese oyster C. angulata and more recently the oyster velar virus disease affecting larval, hatchery-reared Pacific oysters C. gigas. This report presents histo- and cytopathological characteristics of these infections in which large icosahedral cytoplasmic deoxyriboviruses, similar to the iridoviridae, are implicated, The gill necrosis virus causes, principally in the Portuguese oyster, an evolutive ulceration of the gills, including cellular hypertrophy and severe inflammation. Mortalities have been observed in the most serious cases. Hemocytic infection virus has caused mass mortalities of Portuguese oysters in Europe (1970-1974); it induces cytoplasmic lesions in the hemocytes and causes severe injuries to interstitial tissues. Similar infections were observed in 1977 in Pacific oysters. The oyster velar virus develops in the cytoplasm of epithelial cells of the velum and causes tissue lesions. It is the apparent cause of sorne hatchery mortalities.